SCIENTIFIC CONCEPTS OF CYTOKINE GENE EXPRESSION (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Cytokines are signalling molecules of the immune system. The level of expression of these proteins has an important diagnostic value for the selection of immunocorrective therapy and prediction of the intensity and direction of the immune response. In order to determine which cytokines are synthesised and in what quantity, the PCR method is widely used.